Blood Group Antigen Matching Influence on Gestational Outcomes (AMIGO) study. Issue 3 (5th February 2017) - Delaney, Meghan; Wikman, Agneta; van de Watering, Leo; Schonewille, Henk; Verdoes, Jennie P.; Emery, Stephen P.; Murphy, Michael F.; Staves, Julie; Flach, Susanne; Arnold, Donald M.; Kaufman, Richard M.; Ziman, Alyssa; et al.
Abstract : BACKGROUND: Red blood cell (RBC) antigen matching policies to prevent alloimmunization in females of childbearing potential (FCP) vary between centers. To inform transfusion centers responsible for making decisions about matching policies for FCPs, the causal stimulus of the antibodies implicated in severe hemolytic disease of the fetus and newborn (HDFN) must be determined. STUDY DESIGN AND METHODS: We conducted a multinational retrospective study of women with offspring affected by severe HDFN requiring neonatal exchange transfusion and/or intrauterine transfusion. Mothers treated at centers that provide extended antigen‐negative RBCs (MATCH, five centers) and those that do not (NoMATCH, nine centers) were compared. RESULTS: A total of 293 mothers had at least one affected pregnancy: 179 at MATCH centers and 114 at NoMATCH centers. Most alloimmunization (83%) was attributed to previous pregnancy: 3% to transfusion (two cases at MATCH, six at NoMATCH centers) and 14% undetermined (both antecedent transfusion and pregnancy). Only 50 mothers had received transfusions; 13 had HDFN due to anti‐K at MATCH and four at NoMATCH centers. Most (12/13, 92%) of the anti‐K HDFN cases at MATCH centers had K+ paternal antigen status. Mothers at the MATCH centers do not appear to be protected from HDFN due to K, C, c, and E antibodies, although the low number of FCPs who received transfusions precluded drawing firm conclusions. CONCLUSION: The causal stimulus of antibodies that cause HDFN is predominantly from previous pregnancy. Although extended RBC matching for FCPs may impart some protection from allosensitization, we were unable to show a positive effect, possibly because matching policies are not uniform and there was a small number of mothers who previously received transfusions.